Cerclagem cervical em maternidade de referência no Ceará: indicação e desfecho perinatal. - Eufrasio, Cinara Gomes (2021)
Preterm birth remains the main cause of neonatal mortality and morbidity. One way to decrease the number of preterm births is cervical cerclage, for that patients must be selected correctly, and the procedure must be performed at the appropriate time. The objective was to evaluate the clinical and ultrasound findings of patients undergoing cervical cerclage and perinatal outcomes in a tertiary public maternity in Fortaleza-CE. Cross-sectional study was carried out by consulting the medical records of pregnant women who underwent cerclage from 2014 to 2019, in a maternity hospital in Fortaleza-CE. The study included 116 medical records of pregnant women who underwent cerclage at MEAC-UFC in the investigated period whose complete data on the development of single gestation pregnancy and childbirth can be recovered. The medical records were analyzed using a form based on the cervical indications present in the international protocols. Pregnant women were categorized into three groups according to the indication of cerclage: group 1 (history-indicated cerclage), group 2 (ultrasound-indicated cerclage), and group 3 (physical exam-indicated cerclage). The outcome variables were gestational age at delivery, latency period between cerclage and delivery, and perinatal outcome of the newborn. Fisher’s exact test was used for numerical variables, the Kruskal-Wallis H test for independent variables. Spearman’s rank correlation coefficient was adopted to assess the correlation between the variables. The mean gestational age (GA) at which cerclage was performed was 18 weeks (± 4), with a lower GA at cerclage in group 1 (16,6 ± 4). The mean GA at delivery was 34,8 weeks (± 6,2), with the lowest mean GA in group 3 (30,1 weeks ± 8,8). Pregnancy resolution above 37 weeks occurred in 61,7%. The latency period between cerclage and delivery was 129,3 days (± 49,8); in group 1; 101,7 days (± 40,9) in group 2; 49,1 days (± 46,1) in group 3. In the general analysis of indication for cerclage, most pregnant women were recommended for cerclage according to the literature (79,3%). As for the perinatal outcome, 78,3% of newborns (NB) were discharged, 6,1% were transferred, and there were deaths in 15,7% of cases. Regarding the latency period between cerclage and delivery in the three groups, there was a statistically significant difference (p < 0,001). A positive correlation was found between the cervix length and the latency time (r = 0,283) (p = 0,003) in group 2. There was a significant difference in perinatal outcomes between groups, with group 3 having the highest mortality (p = 0,041). Cerclage is recommended even at gestational age different from the one indicated in the literature as long as fetal viability is not guaranteed, as well as in case of patients with cervical dilation or sac protrusion, as a way to increase the chances of mothers having viable pregnancies and ensuring the survival of the newborn.